Pengaruh substitusi ampas tahu pada pakan basal terhadap bobot karkas dan giblet Ayam Broiler - Herlinae Herlinae; Yemima Yemima; Rekki Milano (Fakultas Peternakan Universitas Kristen Palangka Raya, 2019)
The aim of this study was to determine the effect of tofu waste substitution in basal feed on carcass weight and giblets weight of broiler chickens. This study used a completely randomized design with 4 treatments and 5 replications. If it is significant, it will be followed by Duncan's Test. This research was carried out in Practice Field of the Faculty of Animal Husbandry and Palangka Raya Christian University Laboratory. The results showed that the substitution of tofu waste on basal feed greatly influenced carcass and giblets weight, and there was no substitution rate of tofu waste on basal feed which could reach maximum carcass weight and giblets weight. Keywords : Tofu waste, basal feed, carcass, giblets.